2016
DOI: 10.1002/aenm.201600697
|View full text |Cite
|
Sign up to set email alerts
|

Robust Sub‐Monolayers of Co3O4 Nano‐Islands: A Highly Transparent Morphology for Efficient Water Oxidation Catalysis

Abstract: The scalable synthesis of highly transparent and robust sub‐monolayers of Co3O4 nano‐islands, which efficiently catalyze water oxidation, is reported. Rapid aerosol deposition of Co3O4 nanoparticles and thermally induced self‐organization lead to an ultra‐fine nano‐island morphology with more than 94% light transmission at a wavelength of 500 nm. These transparent sub‐monolayers demonstrate a remarkable mass‐weighted water oxidation activity of 2070–2350 A gCo3O4−1 and per‐metal turnover frequency of 0.38–0.62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…[26,28] In this work, the FSP-SnO 2 catalysts were synthesized at a feedrate of 3, 5, and 7 mL min −1 and are denoted as FSP-SnO 2 -3, FSP-SnO 2 -5, and FSP-SnO 2 -7, respectively (detailed in the Experimental Section). By varying the precursor feed rate to the flame, the flame conditions can be controlled and thus allow for the tuning of material properties such as particle size and morphology, crystallinity, and defects.…”
Section: Resultsmentioning
confidence: 99%
“…[26,28] In this work, the FSP-SnO 2 catalysts were synthesized at a feedrate of 3, 5, and 7 mL min −1 and are denoted as FSP-SnO 2 -3, FSP-SnO 2 -5, and FSP-SnO 2 -7, respectively (detailed in the Experimental Section). By varying the precursor feed rate to the flame, the flame conditions can be controlled and thus allow for the tuning of material properties such as particle size and morphology, crystallinity, and defects.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a shows a schematic for the high‐temperature fabrication of the BiVO 4 photoanodes. A flame synthesis setup previously described in detail for the fabrication of ultrafine Co 3 O 4 nano‐islands was used . Here, atomization and combustion of the liquid precursor solution, followed by rapid quenching by the entrained air, results in the nucleation of BiVO 4 clusters of few nanometers, and the latter grow in the gas phase by condensation and Brownian's coagulation.…”
Section: Resultsmentioning
confidence: 99%
“…248,[302][303][304][305][306] Flame spray pyrolysis as an aerosol deposition method is also highly scalable for facile and fast fabrication of various nanostructured (photo)electrodes. [307][308][309][310] A production rate of a few kilograms per hour is achievable using lab-scale burners with tunable specific surface area and catalytic activity of the produced nanomaterials. [311][312] Notably, although the electrocatalysts produced by these industrially viable fabrication techniques demonstrated excellent catalytic activities, 310,313 the photoelectrodes fabricated using them still showed poorer photoactivities than those state-of-the-art photoelectrodes using conventional lab-scale fabrication techniques.…”
Section: Membraneless Electrolyser-based Systemmentioning
confidence: 99%
“…[307][308][309][310] A production rate of a few kilograms per hour is achievable using lab-scale burners with tunable specific surface area and catalytic activity of the produced nanomaterials. [311][312] Notably, although the electrocatalysts produced by these industrially viable fabrication techniques demonstrated excellent catalytic activities, 310,313 the photoelectrodes fabricated using them still showed poorer photoactivities than those state-of-the-art photoelectrodes using conventional lab-scale fabrication techniques. 254 reported that large size led to a significant potential drop for the same photoelectrode (Figure 39a, b).…”
Section: Membraneless Electrolyser-based Systemmentioning
confidence: 99%